Risk Analysis of Waste Management Failure at Al-Hikmah Quran Islamic Boarding School in Bogor Using FMEA and AHP Methods - Rizkiya, Ananda Nurul; Rimantho, Dino (ASTONJADRO, 2024)
The Bogor Al-Hikmah Qur’an Islamic Boarding School is a male-only Islamic boarding school with 160 active students, producing no less than 50 kg of waste per day. Waste management is still carried out traditionally, that is, collected and then burned. Waste management is an important part that needs attention at the Al-Hikmah Quran Islamic Boarding School, Bogor. Therefore, this final project research aims to analyze the factors that have the potential to pose a risk of failure in waste management at the Bogor Al-Hikmah Qur’an Islamic Boarding School, and provide the best alternative that can be used by the Bogor Al-Hikmah Qur’an Islamic Boarding School in managing rubbish. The data used in this study came from literature studies, interviews, and distributing questionnaires to the boarding school. In this study using the fishbone diagram method to identify risks, Failure Mode and Effect Analysis (FMEA) to determine the factors that can cause failure in waste management, and Analytical Hierarchy Process (AHP) to find the best alternative in waste management at the Qur’an Islamic Boarding School and Al-Hikmah Bogor. From the results of this study, it was obtained that the highest Risk Priority Number (RPN) value was 720 on the human factor with the sub factor that there were still many students who littered, and on the method factor with the sub factor there were no regulations for disposing of waste in its place, and alternative solutions for management waste at the Al-Hikmah Quran Islamic Boarding School in Bogor is to conduct training for boarding school residents with a weight of 0.38. The alternative strategy is one of the solutions to solve the problem of plastic waste from students’ rooms with a weight of 0.51. With the training for boarding school residents, it is hoped that the plastic waste produced by the boarding school can be recycled so that it can be reused, and reduce the rate of disposal of plastic waste to landfills.